Formation of tabular plutons - results and implications of centrifuge modelling - Dietl,C.; Koyi,H. (Journal of Geosciences, 2008)
Geophysical investigations reveal that many granitoid plutons possess a tabular shape: either laccolithic, lopolithic or phacolithic. In this study, the results of a centrifuge experiment are used to understand the formation mechanisms of these features. The model was build of a sequence of 14 differently coloured plasticine layers. Two buoyant layers - with a volume of c. 40 cm3 each - were incorporated into the model stratigraphy at different depths to investigate, whether the rise and emplacement of buoyant material at different levels results in different intrusion structures.After centrifuging for 30 min at 700 G, both the buoyant layers had formed two lenticular sills (phacoliths) with aspect ratios (length/thickness) of 6 and 3.4 for the upper and lower phacoliths, respectively, directly above both pre-existing perturbations in the buoyant layers. During their movement, the buoyant phacoliths had pushed their roof plasticine upward. Simultaneously, their floor plasticine had subsided (bottom sinking). Subsidence of the floor material had choked the inflow of further buoyant material into the feeder channel of the developing sills and inhibited their further lateral growth.The observed forced downward movement of the plasticine floor of the forming PDMS (polydimethylsiloxane) phacoliths resembles the so-called “floor depression” of host rock material around an emplacing tabular pluton. Floor depression is supposed to be a very important vertical material transfer process, which provides space for the construction of lopo- and phacoliths. The subsidence of host material made space for the developing buoyant phacoliths, but also restricted their growth to a certain time slot before the influx of new buoyant material into the feeder dyke of the tabular intrusive body was shut off. Similarly, in nature, the growth of a tabular pluton might be limited not only by the rate of magma ascent and its physical properties, but also by the emplacement processes of the evolving pluton.
Keywords: phacoliths; laccoliths; tabular plutons; ascent; emplacement; centrifuge modelling